Exploring the Ways to Build Better Teacher-Student Relationship Since the Resumption of Face-to-Face Classes in Azerbaijan British College - Ahadli, Nigar; Baylarova, Leyla; Imanova, Aytaj (ADA University, 2022)
Many studies have shown that, the teacher-student relationship is one of the most crucial components in student learning. Student's self-regulation abilities, notably autonomy and self-determination, can be aided by constructive teacher-student relationships. As a result of the positive teacher-student relationships, students can achieve their personal and academic goals if they learn to analyze and modify their conduct. Moreover, students who had good relationships with their teachers have gradually improved their behavior. With the aim of creating positive teacher-student relationship, it is important that teachers and students interact in a face-to-face environment. However, transitioning to online setting because of the pandemic has created some challenging relations amid teachers and students. Based on preliminary data collected from the teaching staff of Azerbaijan British College, it was obvious that the secondary school students became more neglectful since traditional classes have started after the lockdowns. Teachers and students have been experiencing similar issues regarding the difficulties caused by the online classes. Nevertheless, when the face-to-face classes have started again, the teacher-student relations were distorted again, as the re adaptation process had to take place. This research comprises interview-based research that analyzes how teacher-student relations have changed since the resumption of face-to-face classes in Azerbaijan British College, and what are some ways that teacher-student relationships can be enhanced. Research recommends dual approach on the advancement of the teacher-student relationship.
Keywords: Education, Higher -- Azerbaijan.; Teacher-student relationship.; Online teaching.; Face-to-face teaching.; Education